INVESTIGASI PERAN EKUITAS, DAN DANA PIHAK KETIGA TERHADAP PERTUMBUHAN PROFIT BANK MUAMALAT INDONESIA TAHUN 2016-2020 - Iqbal Rafiqi; Annisa Annisa; Alfian Rihtuzahrah (Masyrif : Jurnal Ekonomi, Bisnis dan Manajemen, 2021)
Bank Muamalat Indonesia is an Islamic financial institution that continues to increase profits from every financial transaction that occurs between its customers with efforts and efforts to maintain stability in obtaining profits with several instruments, including the two bank financial instruments in this study. The purpose of this study is to find out how the influence of equity and third-party funds on the growth of bank profits in 2016-2020. This research uses quantitative approaches with descriptive methods. The data used is sukender data obtained from bank Muamalat Indonseia's quarterly financial report in 2016-2020. The results of this study concluded that partially (test t) showed that Equity(X1)) had a positive or significant effect on profit growth at Bank Muamalat Indonesia. And showed that DPK(X2) has no significant effect on profit growth at Bank Muamalat Indonesia. Based on the results of the calculation of regression tests together (test F) shows that equity X 1 and DPK X2 simultaneously affect profits on bank muamalat in 2016-2020 (Y). based on the results of the determination coefficient test (R2),the magnitude of the influence of equity and third party funds onbank Muamalat Indonesia's profit growth by 39.3%, while the remaining 60.7% was influenced by other factors outside the study.